Acalypha brachystachya: A Valuable Source for Natural Antioxidants - Hafeez, Irsa; Mariam, Irfana; Riaz, Tauheeda; Athar Abbasi, Muhammad; Zahra Siddiqui, Sabahat; Ajaib, Muhammad; Ahmad, Irshad; Rehman, Aziz-ur (Asian Journal of Chemistry, 2012)
In present investigation, the crude methanolic extracts of seeds, shoot and leaves of Acalypha brachystachya hornem. were fractionated separately with n-hexane, chloroform, ethyl acetate and n-butanol sequentially to obtain various fractions. These fractions were screened for their phyto-constituents and generally found to contain important bioactive substances such as flavonoids, alkaloids, phenols, terpenoids, tannins, saponins and sugars. Then the antioxidant potential of these fractions was assayed by the four methods, namely, DPPH assay, FRAP assay, total phenolic assay and phosphomolybdenum complex assay. Ethyl acetate soluble fraction of seeds exhibited good antioxidant activity, chloroform soluble fractions of seeds and leaves possessed medium activity while all the remaining fractions showed poor activity.